DESA SUNGAI RAMBAI 1960-2021 - Andrean, Muhammad; Azmi, Ulul; Agustiningsih, Nur (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2024)
The purpose of this study is to describe the history of the formation of Sungai Rambai Village to know and describe the development and changes in the socio-cultural life of the residents of Sungai Rambai Village. The research method used historical method which consists of four steps, namely heusristic, criticism, interpretation and historiography. Based on research conducted by the author, it is known that Sungai Rambai Village is one of the villages located in Pengabuan District, West Tanjung Jabung Regency before the expansion in 2008 into Senyerang District which is 69 km from the city center of West Tanjung Jabung Regency. The residents of Sungai Rambai Village are a community group belonging to the Javanese tribe. According to Village Archive Data and information from several communities, Sungai Rambai Village already existed during the Japanese colonial period. The residents of Sungai Rambai Village in an effort to meet their needs can be grouped into several types, namely; areca nut plantations, oil palm, farming, traders, laborers, civil servants, and there are also fishermen as side jobs. However, the majority are farmers (areca nut and oil palm), be they owners or laborers.